Teachers' perceptions about their preparedness to teach and include children with Autism Spectrum Disorder in the regular classroom : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Palmerston North, New Zealand - Apers, Cherie (Massey University, 2016)
This research explored five primary school teachers’ perceptions about their preparedness to teach and include students with Autism Spectrum Disorder in a regular classroom. Taking a qualitative approach, these teachers were interviewed individually using semi-structured interviews, whereby the research methodology followed an appreciative inquiry framework. The use of this framework allowed for the positive aspects of their practices to be revealed. The research discovered that through a combination of prior knowledge and teaching experience, these teachers were able to develop and practice an inclusive pedagogy with strategies that could be utilised, not just for those with a disability, but for all children in their classrooms. While there were some areas where the teachers felt they could do with more support, these were taken on as challenges. The teachers involved demonstrated that inclusion of students with ASD in the regular classroom is possible and that this can be a positive experience that benefits the student with ASD, other students, the teachers themselves, the school, and the wider community.
Keywords: Children with autism spectrum disorders; Education (Elementary); Inclusive education; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education